2014
DOI: 10.1371/journal.pone.0098390
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Rebamipide Eyedrop Administration on Ocular Lesions in a Murine Model of Primary Sjögren's Syndrome

Abstract: BackgroundTopical therapy is effective for dry eye, and its prolonged effects should help in maintaining the quality of life of patients with dry eye. We previously reported that the oral administration of rebamipide (Reb), a mucosal protective agent, had a potent therapeutic effect on autoimmune lesions in a murine model of Sjögren's syndrome (SS). However, the effects of topical treatment with Reb eyedrops on the ocular lesions in the murine model of SS are unknown.Methods and FindingReb eyedrops were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 37 publications
(42 reference statements)
1
22
0
1
Order By: Relevance
“…In patients with SSDE, chronic ocular inflammatory lesions involve injury to the epithelial cells of the conjunctiva and cornea. [10] As a result, ocular manifestations in SSDE are commonly more severe than in non-SSDE conditions [11, 12]. Patients with SSDE, who often continue to experience ocular symptoms despite extended use of palliative treatments, such as artificial tears, punctual occlusion, and acupuncture [13], may be prone to excessive medical behavior and high levels of mental stress.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with SSDE, chronic ocular inflammatory lesions involve injury to the epithelial cells of the conjunctiva and cornea. [10] As a result, ocular manifestations in SSDE are commonly more severe than in non-SSDE conditions [11, 12]. Patients with SSDE, who often continue to experience ocular symptoms despite extended use of palliative treatments, such as artificial tears, punctual occlusion, and acupuncture [13], may be prone to excessive medical behavior and high levels of mental stress.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, there is little data available in the literature about effects of rebamipide on IL-10. Arakaki et al (2014) reported rebamipide up-regulated IL-10 expression in eye lesions. However, in contrast to the results reported here, Aihara et al (1998) noted that rebamipide suppressed production of IL-10 (as well as of TNF and IL-1).…”
Section: Discussionmentioning
confidence: 99%
“…The drug is also effective as an anti-inflammatory agent and has been useful in the treatment of inflammatory diseases such as colitis (Kishimoto et al 2000) and mucositis (Kim et al 2015). This anti-inflammatory effect is associated with an inhibition of cytokine-mediated neutrophil infiltration, inhibition of reactive oxygen species (ROS) release (Sakurai et al 1998) and induction of IL-10 (Arakaki et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After fluorescein staining, the cornea was examined for corneal epithelial disorders using a slit-lamp microscope with a blue filter which was evaluated using a previously described method with modifications [11]. …”
Section: Methodsmentioning
confidence: 99%